Is the perception of leaving the job of the lecturers influenced by quality work of life? - Julianti Kasih; Teddy Marcus Zakaria (Jurnal Manajemen Maranatha, 2021)
We know the lecturer workforce turnover for a university has considerable trouble. The lecturers' rapid turnover will influence the teaching process's stability. To shorten the lecturer workforce's turnover, the university desires to have an effort to enhance the quality of the lecturers' work-life. This research decides to create life's variables, which is a variables aspect for Maranatha Christian University lecturers to resign from their jobs. Using a survey method to get the data, it distributed questionnaires to 150 lecturers from Maranatha Christian University. The data collected were treated using Amos 22 software. The supervision style and job satisfaction variables' correlation results showed 5.33 and the relationship between salary allowances and supervision style showed a precise result. The conclusion obtained for Maranatha Christian University's lecturers, the quality of work-life, appears not instantly to touch lecturers' desire to move their jobs. However, the supervision and calculation of allowance salaries directly affect job satisfaction, although this relationship realistic presently affects lecturers to drop their jobs. The purpose of this research is to provide information for Maranatha Christian University. This research aims to scale down the lecturers' workforce turnover by increasing the quality work of life variables.